Strategic Managerial Incentive Compensation in Japan: Relative Performance Evaluation and Product Market Collusion - Joh, Sung Wook (The Review of Economics and Statistics, 1999)
In an oligopolistic product market, shareholders strategically use information on rival firms'performances when designing management-incentive contracts. When shareholders use industry performance information through relative performances evaluation (RPE), they evaluate their manager's effort more easily, but hinder collusive behavior in the product market. However, when compensation is positively linked to the industry performance through strategic group performance evaluation (SGPE), the credibility of a manager's commitment to product market collusion increases, and the sustainability of a collusive outcome increases. I test how industry performance affects management-incentive compensation using the data from 796 Japanese firms during the period 1968 to 1992. The results show that management compensation is positively linked to industry profit, suggesting the use of SGPE in management-incentive compensation. Cross-sectional analysis shows that the positive effect of industry profit on management compensation is higher in competitive industries than in concentrated industries. The positive effect is greater in slow-growing industries than in fast-growing industries. Empirical tests incorporating the risk component method show the same results. These results are consistent with the argument that, in a growing market or in a concentrated market, the value of SGPE diminishes as the value of commitment to collusion diminishes.